PROJETA platform: accessing high resolution climate change projections over Central and South America using the Eta model - Holbig, Carlos Amaral; Mazzonetto, Angela; Borella, Felipe; Pavan, Willingthon; Fernandes, José Maurício Cunha; Chagas, Diego José; Gomes, Jorge Luis; Chou, Sin Chan (Agrometeoros, 2018)
The search for data on climate change by researchers, government agencies or private companies is a recurrent demand. However, it is hampered by the means of access to this type of information, mainly due to the complexity of extracting, reformatting, and making this data available, which can exceed terabytes in size. The PROJETA platform aims to automate the process of extracting and making available the dataset of global climate change projections downscaling to 20 km over South America generated by the model Eta at CPTEC/INPE. The data request, processing, and conversion process, which used to be done manually and in a oneto-one data delivery basis. The objective of this work is to describe the methodology used to create the platform PROJETA and the information made available. It is a service that allows access to a broad set of different climatic variables. This dataset is available to different users via the Web or API, in a flexible way in terms of data format and data volume. In addition, it integrates technologies that allow the access to the database in an efficient and easy way for use in studies of impact, vulnerability, and adaptation to climate change in various socio-economic sectors.